Answer:
D) -4x+14
Step-by-step explanation:
We are given with the expression
3 - (4x - 5) + 6
Here we are going to open the bracket at first step
as we have a negative sign in front of bracket the signs of the terms inside brackets will be reversed
3-4x+5+6
now we bring the like terms together
3+5+6 - 4x
Here 3, 5, 6 all are constant and hence like
14-4x
or
3 - (4x - 5) + 6= -4x+14
Hence our answer is -4x+14
Answer:
220 i think but im not sure
Step-by-step explanation:
Answer:
i cant view it
Step-by-step explanation:
Answer:
<em>The base is 24 cm long.</em>
Step-by-step explanation:
<u>Equations</u>
Let's call
b= base of the triangle
h=height of the triangle
The base is 9 cm longer than the height, thus:
b = h + 9
The area of the triangle is:
![\displaystyle A=\frac{bh}{2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20A%3D%5Cfrac%7Bbh%7D%7B2%7D)
![\displaystyle A=\frac{(h+9)h}{2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20A%3D%5Cfrac%7B%28h%2B9%29h%7D%7B2%7D)
And its value is 180:
![\displaystyle \frac{(h+9)h}{2}=180](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B%28h%2B9%29h%7D%7B2%7D%3D180)
Multiplying by 2:
![(h+9)h=360](https://tex.z-dn.net/?f=%28h%2B9%29h%3D360)
Operating:
![h^2+9h-360=0](https://tex.z-dn.net/?f=h%5E2%2B9h-360%3D0)
Factoring:
![(h-15)(h+24)=0](https://tex.z-dn.net/?f=%28h-15%29%28h%2B24%29%3D0)
The only valid positive solution is:
h = 15 cm
And b = h + 9 = 24
b = 24 cm
The base is 24 cm long.